(untitled) (Journal of Pathology of Nepal, 2019)
Background: Fine needle aspiration cytology has become an indispensable tool for diagnosis of intrathoracic lesions. The purpose of this study was to evaluate the spectrum of intrathoracic lesions by image guided fine needle aspiration cytology. Materials and Methods: This was a prospective study of 100 patients, who underwent image guided fine needle aspiration cytology of intrathoracic lesions from December 2015 to November 2016 in the Department of Pathology, Institute of Medicine, Tribhuwan University Teaching Hospital. Results: Of the 100 cases, diagnostic material was obtained in 86 cases, which included 69 cases (80.23%) from lung, 7 cases (8.13%) from pleura and 10 cases (11.62%) from mediastinum. Lung lesions constituted of 61 neoplastic lesions (88.40%), 3 cases (4.34%) suspicious of malignancy, 3 cases (4.34%) negative for malignancy and 2 non- neoplastic lesions (2.89%). Squamous cell carcinoma was the most common lesion of the lung. Pleural lesions consisted of 5 neoplastic cases (71.42%), 1 non- neoplastic case (14.28%) and 1 negative for malignancy (14.28%). Mediastinal lesions consisted of 7 neoplastic lesions (70.00%) and 3 non- neoplastic lesions (30.00%). Biopsy for histopathological examination was available in 30 cases. The concordance of diagnosis of lung lesions by fine needle aspiration cytology and histopathology was 90.90%. Image guided FNAC had sensitivity of 95.83% and specificity of 50.33% in diagnosing intrathoracic lesions. The positive predictive value of image guided FNAC in diagnosis of intrathoracic lesions was 92.00% and negative predictive value of 66.67 percent. Conclusions: Image guided fine needle aspiration cytology of intrathoracic lesions permits categorization and distinction between non- neoplastic and neoplastic lesions.